Multi-objective optimization in metabolism of citric acid production by Aspergillus niger - Martinez, Ginaline C. Ligsanan (Institute of Mathematics, College of Science, University of the Philippines Diliman, 2013)
Citric acid is a compound that plays an important role in chemical processes in many industrial applications because of its ability to easily bond with minerals and metals. It is an intermediate in the citric acid cycle, also known as tricarboxylic acid cycle, and occurs in the metabolism of all plants and animals. In the production of citric acid, the fungus Aspergillus niger has been employed for many years.At present, A. niger remains the main industrial producers of citric acid. In this thesis, we explore the possibility of maximizing the citric acid production of A. niger using a mathematical model of citric acid production and by proposing a multi-objective function and its solution. The mathematical mode that we use is based on the formulation of Nestor Torres et.al. (2000) where they derived a mechanistic model using the S-system framework of the main metabolic pathway involved in citric acid synthesis.